Evaluation of systemic inflammation markers in patients with Hashimoto's thyroiditis - Bozdag, Ahmet; Bozdag, Pinar Gundogan (Sage Publications Ltd, 2024)
Objective To investigate markers of systemic inflammation and the effect of thyroid dysfunction on these parameters in patients with Hashimoto's thyroiditis (HT).Methods Patients with HT and volunteer healthy individuals admitted to the general surgery outpatient clinic between January 2020 and June 2023 were enrolled into the study. Patients with HT were divided into euthyroid, hypothyroid, and hyperthyroid subgroups. All participant data were retrospectively extracted from the hospital database.Results A total of 268 patients (euthyroid, n = 131; hypothyroid, n = 83; and hyperthyroid, n = 54) and 124 controls were included. The platelet-to-lymphocyte ratio was lower in the euthyroid group versus control group, and the neutrophil-to-lymphocyte ratio was lower in controls than the three patient subgroups. Euthyroid and hypothyroid patients with HT exhibited a higher systemic inflammation index than the control group. The pan-immune inflammation index was lower in controls than in euthyroid, hypothyroid, and hyperthyroid patients with HT. In patients with HT, inflammation markers did not significantly differ between subgroups.Conclusions Markers of systemic inflammation provide meaningful and reliable information in patients with HT, but do not differentiate between euthyroid, hypothyroid, or hyperthyroid patients.
Keywords: Hashimoto's thyroiditis; systemic inflammation; hypothyroidism; inflammatory index; pan-immune inflammation